E-yearbook of food and natural resource statistics for 2017 : Statistical facts on agriculture, forestry, fisheries and hunting in Finland - (:unkn) unknown (Luonnonvarakeskus, 2018)
The e-yearbook of food and natural resource statistics is an annual compilation published by the Natural Resources Institute Finland (Luke). This is Luke’s third publication of this kind. The publication portrays Finnish bioeconomy and natural resource statistics on agriculture and the food processing industry, the forest sector, and the game and fisheries industry. The publication contains links to our online statistical database. Luke’s statistical e-yearbook is available in the Natural Resources Institute Finland’s statistics portal at stat.luke.fi/en/. A printed version can be ordered via Luke’s online shop. In the electronic version of the statistical yearbook, links to tables in the online service provide access to up-to-date statistics. Instructions on using the statistics database are available in our online portal. The editor-in-chief of this yearbook was Development Manager Tarja Kortesmaa, and the text was edited by Communications Specialist Aimo Jokela and Senior Communications Specialist Riitta Salo-Kauppinen. Several of Luke’s statistical experts and researchers contributed to the contents and analyses presented in the publication. The layout was designed by Publication Specialist Irene Murtovaara and the infographics by Graphic Design Specialist Essi Puranen. I would like to thank everyone who contributed to this publication and to Luke’s statistics in general for their excellent work and know-how. Feedback and suggestions concerning the publication and our website can be sent by email to tietopalvelu@luke.fi.
Keywords: food; natural resource; agriculture; forestry; fisheries; hunting; statistics